Aerodynamic forces on railway acoustic barriers. Issue 191 (August 2019) - Soper, David; Gillmeier, Stefanie; Baker, Chris; Morgan, Thomas; Vojnovic, Luka
Abstract: Aerodynamic measurements were conducted to assess the magnitude of pressures measured on a range of acoustic barriers during normal working traffic. A week of measurements were made at a number of tests sites, capturing data for a range of train types. The different test sites allowed for a novel assessment of the influence of barrier distance from centre of track and any influence from other trackside infrastructure. Results exhibited a characteristic pressure development measured on the acoustic barrier, as observed in previous studies, with similar magnitudes recorded for all high speed passenger trains. Pressure magnitudes were largest around the train nose and tail regions. A twelve car train had an additional large peak due to the coupling of two six car sets. As barrier distance from centre of track was increased the magnitude of pressures measured was shown to decrease. Fitting a curve of best fit to the results indicated that the same curve form could be used for both the positive and negative nose pressures. Differences in peak pressure magnitudes were observed for results measured underneath the footbridge suggesting a potential influence of the footbridge on the aerodynamic flow development. CEN standards were shown to offer a good estimation to the pressure coefficient measured on the barrier at most positions analysed. Analysis of peak pressure magnitudes in relation to the number of train passes across the barrier life span, calculated through a rainflow analysis, suggested that small pressure fluctuations were the dominant feature across all measurements. Larger fluctuations depended on train type and as such load calculations should account for the different types of traffic observed on the railway. Highlights: An assessment of pressure loads acting on acoustic barriers on high speed railways. An assessment of the influence of barrier distance from centre of track and other trackside infrastructure. Comparison of absorptive and reflective type barriers exhibited similar pressure development and peak magnitudes. With increasing height pressure amplitudes and corresponding cycles decrease. Large pressure fluctuations depend on train type and load calculations should account for different types of traffic.